2011
DOI: 10.1097/ccm.0b013e318218a1ae
|View full text |Cite
|
Sign up to set email alerts
|

Real-time ultrasound-guided subclavian vein cannulation versus the landmark method in critical care patients: A prospective randomized study*

Abstract: The present data suggested that ultrasound-guided cannulation of the subclavian vein in critical care patients is superior to the landmark method and should be the method of choice in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
287
8
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 330 publications
(316 citation statements)
references
References 24 publications
12
287
8
9
Order By: Relevance
“…Clinical examples include the internal jugular vein (Fig. 1), the external jugular vein, the innominate vein [40], the subclavian vein [18,41], the axillary/subclavian veins ( Fig. 2) and the cephalic vein.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical examples include the internal jugular vein (Fig. 1), the external jugular vein, the innominate vein [40], the subclavian vein [18,41], the axillary/subclavian veins ( Fig. 2) and the cephalic vein.…”
Section: Recommendationsmentioning
confidence: 99%
“…Although most of the randomised clinical trials carried out in this area have focused on the internal jugular vein [9-12, 34, 36, 59, 60] and-to a lesser extent-on the subclavian vein [9,41] and the femoral vein [6], it is likely that with growing clinical experience the benefits of ultrasound-guided venipuncture can be extended to all venous access sites.…”
Section: Integration In Clinical Practicementioning
confidence: 99%
“…A recent randomized prospective study showed that ultrasound-guided subclavian catheterization was superior to landmark-based insertion, with a higher rate of success (100 vs. 87.5 %), lower rates of postprocedural pneumothorax (0 vs. 4.9 %), and fewer venipunctures [14].…”
Section: Subclavian Veinmentioning
confidence: 99%
“…In 1986, Yonei et al [8] first described the use of real-time, two-dimensional ultrasound for cannulating the same vein. Since then, a number of studies [9][10][11][12][13][14] have demonstrated that real-time ultrasound guidance and, to a slightly lesser extent, ultrasound assistance markedly reduce the mechanical, infectious, and thrombotic complications of the central venous catheterization [15][16][17]. Compared with the conventional blind insertion, ultrasound assistance can also reduce the rates of catheterization failure and incorrect catheter placement, increase the likelihood of success at the first pass, shorten procedure times, and reduce costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation